How to expect God"s reign to come: From Jesus" through the ecclesial to the cosmic body - Urbaniak, Jakub (HTS teologiese studies, 2016)
This study seeks to articulate the universality of the eschatological expectation, in its specifically Christian form, by interpreting it from the perspective of a radical embodiment. This can be understood in a twofold manner. Firstly, the mysterious reality of the eschatological reign of God is rooted in – and thus can be more adequately grasped through the lens of – Jesus’ own body seen as distinct yet not separate from his risen body and, mutatis mutandis, from his extended body, both ecclesial and cosmic. Secondly, for the eschatological expectation to be lived out in an incarnational way, it must be ‘enfleshed’ in actions aimed at social and ecological liberation.The article consists of four sections. Firstly, we explain in what sense body – and more specifically Jesus’ body – is used in our analysis as a hermeneutic key to notions such as ‘risen body’, ‘spiritual body’, ‘extended body’, ‘social body’, ‘ecclesial body’, ‘cosmic body’, basar/kol basar (‘flesh’/‘all flesh’), and ‘life’. Then, the universality of the eschatological expectation is being articulated on two levels, namely, (1) with regard to the social, and in particular the ecclesial, body, and (2) with regard to the cosmic body, with ecological implications inherent in such perspective. Finally, we close the loop by briefly revisiting the notion of Jesus’ body.